Entre chegar e permanecer: a importância dos apoiadores de alunos com deficiência na Universidade Federal da Paraíba - Costa, Luana Ranielle Ferreira da (2020)
The National Student Assistance Program (PNAES), instituted by Decree number 7,234/2010 that predicts among other objectives to democratize the conditions for the permanence of young people in federal public higher education, (PNAES) has also made it possible for Brazilian students with disabilities in public higher education to receive assistance. In this context, this research is placed in the field of studies related to Inclusive Education, in order to consider that access is related to the conditions of permanence guaranteed through resources and practices for the effectiveness of public inclusion policies. Through this investigative procedure, our main objective was to analyze the importance of the supporters' actions for the permanence of students with disabilities at the Universidade Federal da Paraíba (UFPB). It is a qualitative research in which the theoretical framework is based on discussions about inclusion and permanence in Higher Education. Thus, we have many sources from several authors such as Aranha (1995), Dantas (2014, 2019), Corrêa (2010), Dias Sobrinho (2010), Sassaki (2003, 2010), Skliar (2006), Veiga-Neto (2001a, 2001b), among others. In addition, the normative basis is presented at a national level and specifically at UFPB, such as laws, decrees, resolutions, plans and other legal mechanisms relevant to the object of study. The production of data was carried out through semi-structured interviews applied to the research subjects: supported students and supporters of Campus I of UFPB. In analysis of the interviews, it uses the Content Analysis Technique proposed by Bardin (2011), which provides for three fundamental phases: 1) preanalysis; 2) exploration of the material and 3) treatment of the results - inference and interpretation. The analysis showed the need for training for inclusion, which is fundamental for overcoming challenges and solving difficulties presented, especially in the first experiences related to support. We have also identified that such training should cover not only supporters or teachers, but the University community as a whole, considering that inclusion is a collective responsibility.